Patterns of visual field changes in thyroid eye disease. (4th July 2017) - Choi, Catherine J.; Oropesa, Susel; Callahan, Alison B.; Glass, Lora R.; Teo, Livia; Cestari, Dean M.; Kazim, Michael; Freitag, Suzanne K.
ABSTRACT: This article provides a systematic description of visual field changes in thyroid eye disease-compressive optic neuropathy (TED-CON). A retrospective, non-comparative chart review of patients with TED-CON and documented Humphrey Visual Field 24-2 or 30-2 testing was conducted with IRB approval. Ninety-six visual fields in 68 patients were classified into 7 broad categories (superior, inferior, diffuse, temporal, nasal, central/paracentral, enlarged blind spot) and 17 mutually exclusive patterns from the Ocular Hypertension Treatment Study (OHTS) or "other." Fifty-three of 96 visual fields (55%) showed an inferior defect using the broad categories, with the remaining 6 categories ranging from 2% to 14%. The five most common OHTS patterns were other (28%), partial arcuate (28%), partial peripheral rim (9%), arcuate (8%) and altitudinal (7%). Further sub-classification showed a predominance of inferior visual field defects, ranging from 33% to 93% of each category. Of the 78 visual fields in these five categories combined, 52 (67%) were inferior defects. Inferior defect is the most typical TED-CON-associated visual field change. While the OHTS categories are geared toward classification of glaucomatous patterns, the overall predominance of inferior field defects in TED-CON was clearly demonstrated. These "other" visual field changes showing central inferior defect up to but not crossing the horizontal meridian and not contiguous from blind spot to nasal meridian should be designated as "TED-CON pattern." The high proportion of visual fields falling under the "other" category, however, does demonstrate the need for a more specific and tailored visual field classification system for TED-CON.